Praktikum jarak jauh pada perkuliahan apresiasi menghias kain dengan video blog - Permata, Ratih Swastika; Nawimar, Wesnina; Moerdisuroso, Indro (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Online learning in Fashion Design Vocational School finds challenges in its application, especially in the practical learning method. One of the strategies used in practicum is by using video blogs in the process of delivering a practical lesson. This study aimed to find student perceptions in learning that utilizes online video blogs, the process of transmitting meaning on distance learning, and advantages and disadvantages of video blogs. There were 5 participants and 1 source person. The methods of data collection were conducted by doing interview, participatory observation, and documentation studies. The method employed in this study was a qualitative case study method conducted in the Decorating Cloth Appreciation class in the 2020/2021 Academic Year. The results showed that: (1) There were positive perceptions in online practicums related to teaching and learning aspects and the delivery of material with vlogs, negative perceptions were found on aspects of internet network limitations and student learning facilities during online learning. (2) The process of transmitting meaning was supported by instructional communication between educators and students. (3) The advantages of video blog media were in the aspect of delivering easy-to-understand content, the flexible and repetitive nature of the media user online. The lack of video blog media lies in the uneven understanding of students, especially in practicum cases which often lead to different findings in practice. It can be concluded that the use of video vlogs can be an alternative learning resource in distance practicum learning.